Ginkgo biloba L. Prevents Hypobaric Hypoxia–Induced Spatial Memory Deficit Through Small Conductance Calcium-Activated Potassium Channel Inhibition: The Role of ERK/CaMKII/CREB Signaling - Kushwah, Neetu; Jain, Vishal; Kadam, Manisha; Kumar, Rahul; Dheer, Aastha; Prasad, Dipti; Kumar, Bhuvnesh; Khan, Nilofar (Frontiers in Pharmacology, 2021)
Hypobaric Hypoxia (HH) is a stressful condition, which is more common at high altitudes and can impair cognitive functions. Ginkgo biloba L leaf extract (GBE) is widely used as herbal medicine against different disorders. Its ability to improve cognitive functions, reducing oxidative stress, and promoting cell survival, make it a putative therapeutic candidate against HH. The present study has been designed to explore the effect of GBE against HH-induced neurodegeneration and memory impairment as well as possible signaling mechanisms involved. 220-250 gm (approximately 6-8-week-old) Sprague-Dawley rats were randomly divided into different groups. GBE was orally administered to respective groups at a dose of 100 mg/kg/day throughout the HH exposure i.e. 14 days. Memory testing was performed followed by hippocampus isolation for further processing for different molecular and morphological parameters related to cognition. Results indicated that GBE ameliorated HH-induced memory impairment, oxidative damage, and reduced apoptosis. Moreover, GBE modulates the activity of the small conductance calcium-activated potassium channels, which further reduces glutamate excitotoxicity and apoptosis. The exploration of the downstream signaling pathway demonstrated that GBE administration prevents HH-induced small conductance calcium-activated potassium channels activation and that initiates pro- survival machinery by activating extracellular signal-regulated kinase (Erk)/calmodulin-dependent protein kinase II (CaMKII) and cAMP response element-binding protein (CREB) signaling pathway. In summary, the current study demonstrates the beneficial effect of GBE against conditions like HH and provides various therapeutic targets involved in the mechanism of action of GBE-mediated neuroprotection.